2001
DOI: 10.2134/jeq2001.3051790x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Losses from Grasslands Fertilized with Broiler Litter: EPIC Simulations

Abstract: Broiler litter, a mixture of poultry excreta and bedding material, is commonly used to fertilize grasslands in the southeastern USA. Previous work has shown that under certain situations, application of broiler (Gallus gallus domesticus) litter to grasslands may lead to elevated levels of phosphorus (P) in surface runoff. The EPIC simulation model may be a useful tool to identify those situations. This work was conducted to evaluate EPIC's ability to simulate event and annual runoff volume and losses of dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
(33 reference statements)
0
31
0
1
Order By: Relevance
“…EPIC has been applied throughout the U.S. and many other countries (Bernardo et al, 1993;Sugiharto et al, 1994;King et al, 1996;Potter et al, 1998;Brown and Rosenberg, 1999;Pierson et al, 2001;Bernardos et al, 2001;Rinaldi, 2001;Chung et al, 2002;ApezteguĂ­a et al, 2002). The model has been integrated into the Resources and Agricultural Policy System (RAPS) designed to evaluate the economic and environmental impacts of agricultural polices for the north central U.S. (Babcock et al, 1997).…”
mentioning
confidence: 99%
“…EPIC has been applied throughout the U.S. and many other countries (Bernardo et al, 1993;Sugiharto et al, 1994;King et al, 1996;Potter et al, 1998;Brown and Rosenberg, 1999;Pierson et al, 2001;Bernardos et al, 2001;Rinaldi, 2001;Chung et al, 2002;ApezteguĂ­a et al, 2002). The model has been integrated into the Resources and Agricultural Policy System (RAPS) designed to evaluate the economic and environmental impacts of agricultural polices for the north central U.S. (Babcock et al, 1997).…”
mentioning
confidence: 99%
“…Edwards Crop yields; N runoff losses and organic N losses; 1,500 EPIC simulations that were representative of region Atwood et al (1999) et al (1994) found that annual EPIC estimates of nutrient losses were significantly correlated with measured values, except for nitrate-N. Relatively strong agreement was found by Pierson et al (2001) between EPIC-predicted and measured phosphorus (P) losses in runoff, but predictions for single events were not as accurate. Long-term trends were accurately predicted by EPIC for conditions at Treynor, Iowa (Chung et al, 1999), although predicted annual losses were not as accurate.…”
Section: Nutrient Cycling and Nutrient Loss Studiesmentioning
confidence: 99%
“…Example applications include assessment of sediment and nutrient losses as a function of different tillage systems, crop rotations, and fertilizer rates King, Richardson, and Williams 1996); nutrient losses from livestock manure applications (Edwards et al 1994;Pierson et al 2001); nitrate-nitrogen (NO 3 -N) losses through subsurface tile drainage (Chung et al 2001;Chung et al 2002); nutrient cycling as a function of cropping system (Cavero et al 1999;Bernardos et al 2001); soil loss due to wind erosion (Potter et al 1998;Bernardos et al 2001); climate change impacts on crop yield and/or soil erosion (Favis-Mortlock et al 1991;Brown and Rosenberg 1999); losses from field applications of pesticides (Williams, Richardson, and Griggs 1992;Sabbagh et al 1992); irrigation impacts on crop yields (Cabelguenne, Jones, and Williams 1995;Rinaldi 2001); estimation of soil temperature (Potter and Williams 1994;Roloff, de Jong, and Nolin 1998a); and soil carbon sequestration as a function of cropping and management systems (Lee, Phillips, and Liu 1993;ApezteguĂ­a, Izaurralde, and Sereno 2002). The flexibility of EPIC has also led to its adoption within several integrated economic and environmental modeling systems that have been used to evaluate agricultural policies at the farm, watershed, and/or regional scale (e.g., Taylor, Adams, and Miller 1992;Bernardo et al 1993;Foltz, Lee, and Martin 1993;Babcock et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive manure applications in these areas often exceed the capacity of the soils to retain nutrients. Repeated applications of excess manure can increase P losses in runoff (Sharpley et al, 2001;Pierson et al, 2001) to stream and river waters, with significant consequences for downstream water quality.…”
Section: Introductionmentioning
confidence: 99%